Carcinoid tumor ofthe kidney. Report of a case and literature review - Vieira, Sabas Carlos (2022)
Carcinoid tumor of the kidney is extremely rare and its diagnosis may pitzzle physicians and pathologists. The case of a 54-year-old female patient with an incidental finding of renal carcinoid tumor is presented and literature is reviewed. The patient underwent radical nephrectomy with lymphadenectomy, and there are no signs of active disease in a 5-year follow-up.